Non-integrating episomal plasmid-based reprogramming of human amniotic fluid stem cells into induced pluripotent stem cells in chemically defined conditions. Issue 2 (17th January 2016) - Slamecka, Jaroslav; Salimova, Lilia; McClellan, Steven; van Kelle, Mathieu; Kehl, Debora; Laurini, Javier; Cinelli, Paolo; Owen, Laurie; Hoerstrup, Simon P; Weber, Benedikt
ABSTRACT: Amniotic fluid stem cells (AFSC) represent an attractive potential cell source for fetal and pediatric cell-based therapies. However, upgrading them to pluripotency confers refractoriness toward senescence, higher proliferation rate and unlimited differentiation potential. AFSC were observed to rapidly and efficiently reacquire pluripotency which together with their easy recovery makes them an attractive cell source for reprogramming. The reprogramming process as well as the resulting iPSC epigenome could potentially benefit from the unspecialized nature of AFSC. iPSC derived from AFSC also have potential in disease modeling, such as Down syndrome or β-thalassemia. Previous experiments involving AFSC reprogramming have largely relied on integrative vector transgene delivery and undefined serum-containing, feeder-dependent culture. Here, we describe non-integrative oriP/EBNA-1 episomal plasmid-based reprogramming of AFSC into iPSC and culture in fully chemically defined xeno-free conditions represented by vitronectin coating and E8 medium, a system that we found uniquely suited for this purpose. The derived AF-iPSC lines uniformly expressed a set of pluripotency markers Oct3/4, Nanog, Sox2, SSEA-1, SSEA-4, TRA-1-60, TRA-1-81 in a pattern typical for human primed PSC. Additionally, the cells formed teratomas, and were deemed pluripotent by PluriTest, a global expression microarray-based in-silico pluripotency assay. However, we found that the PluriTest scores were borderline, indicating a unique pluripotent signature in the defined condition. In the light of potential future clinical translation of iPSC technology, non-integrating reprogramming and chemically defined culture are more acceptable.